Prokaryotes in Subsoil—Evidence for a Strong Spatial Separation of Different Phyla by Analysing Co-occurrence Networks - Uksa, Marie; Schloter, Michael; Endesfelder, David; Kublik, Susanne; Engel, Marion; Kautz, Timo; Köpke, Ulrich; Fischer, Doreen (Frontiers in Microbiology, 2015)
Soil microbial communities provide a wide range of soil functions including nutrient cycling, soil formation, and plant growth promotion. On the small scale, nutrient rich soil hotspots developed from soil animal or plant activity are important drivers for microbial communities and their activity pattern. Nevertheless, in subsoil, the spatial heterogeneity of microbes with diverging lifestyles has been barely considered so far. In this study, the phylogenetic composition of the bacterial and archaeal microbiome based on 16S rRNA gene pyrosequencing was investigated in the soil compartments bulk soil, drilosphere, and rhizosphere in topsoil and in the subsoil of an agricultural field. With co-occurrence network analysis, the spatial separation of typically oligotrophs and heterotrophs in subsoil and hotspots was assessed. Four co-occurring bacterial communities were identified and attributed to bulk topsoil, bulk subsoil, drilosphere, and rhizosphere. The bacterial phyla Proteobacteria and Bacteroidetes, which represent many copiotrophic bacteria, are affiliated to the hotspot communities – the rhizosphere and drilosphere – both in topsoil and subsoil. Acidobacteria, Actinobacteria, Gemmatimonadetes, Planctomycetes, and Verrucomicrobia with many oligotrophic bacteria, are the abundant groups of the bulk subsoil community. The bacterial core microbiome in this soil was estimated and only covers 7.6% of the bacterial sequencing reads but includes both oligotrophic and copiotrophic bacteria. Instead, the archaeal core microbiome includes 56% of the overall archaeal diversity and comprises only the ammonium oxidizing Nitrososphaera. Thus, the spatial variability of nutrient quality and quantity strongly shapes the bacterial community composition and their interaction in subsoil, whereas archaea are a stable backbone of the soil prokaryotes.